Optimisation of container inspection system in a port - Ong, Wen Xiang. (2011)
The onset of globalisation coupled with the advent of containerisation fuelled the rise of the maritime and shipping industry. The world has become so heavily reliant on the shipping of containers that it accounts for the largest proportion of all the cargos that need to be transported around the globe and this has adversely resulted in the possibility of terrorists taking advantage of their strategic economic importance through sabotage and using it as a channel to cause widespread devastation and destruction. The September 11 terrorist attacks in year 2001 on the United States have clearly demonstrated that threats of terrorism are very real and that no country is completely invulnerable to it. Thus there exists the need for a comprehensive, cost-effective and robust container inspection system. The author, utilising only two types of inspection devices, proposed 6 unique check station configurations for the inspection system through the incorporation of Boolean OR and AND terminologies. Using the methodologies of Operations Research and Linear Programming, cost modeling was then performed based on the cost parameters of initial deployment, operations and system performance to find the optimal expected cost of inspection per container. Using Microsoft Excel 2010’s Solver Add-In, the linear program was solved and the minimum expected cost of inspection per container was obtained using the most optimum check station configurations and overall strategy. The author then performed numerical analyses to compare the author’s proposed model and models using only Boolean OR and AND concepts, and to study the sensitivity effects and relationships between the various parameters used in the modeling process, including the effects of false clear upper bound, probability of threat, prices of devices and the system parameters.